2016
DOI: 10.2174/1573403x12666160606122451
|View full text |Cite
|
Sign up to set email alerts
|

Towards Optimal Heart Failure Care: Couples-Oriented Strategies to Improve Patient Adherence and Health Outcomes

Abstract: Psychosocial factors play an important role in the development and progression of cardiovascular diseases (CVD), such as chronic heart failure (CHF). In particular, psycho-cognitive disturbance is common in CHF, which presents additional challenges to secondary prevention and management strategies. This review provides a summary of the contemporary psycho-cardiology literature, including coverage of common mood and cognitive symptoms, and explores some of the pathophysiologic evidence linking psycho-cognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 80 publications
2
11
0
Order By: Relevance
“…Recent research, however, suggests that including family caregivers in the disease management of patients with HF may improve outcomes. 51 In this article, the one study that reported no significant improvement in attitudes toward DNR and hospice enrollment 38 highlighted a social discordance among the limitations: that the patient population was predominantly African American whereas the providers were mostly Caucasian. The authors recommended that future studies should include more diverse palliative care teams.…”
Section: Fig 2 Meta-analysis Of Readmissionsmentioning
confidence: 94%
“…Recent research, however, suggests that including family caregivers in the disease management of patients with HF may improve outcomes. 51 In this article, the one study that reported no significant improvement in attitudes toward DNR and hospice enrollment 38 highlighted a social discordance among the limitations: that the patient population was predominantly African American whereas the providers were mostly Caucasian. The authors recommended that future studies should include more diverse palliative care teams.…”
Section: Fig 2 Meta-analysis Of Readmissionsmentioning
confidence: 94%
“…As self-management takes place in the context of families, family members, especially spouses, play a pivotal role in working with their loved ones in the management of chronic disease conditions [6,7]. As such, the strained health workers shall leverage the daily interactions between the older couple, and incorporate the mutual efforts of the couple into the management plan.…”
Section: Significance Of Spouse In Chronic Disease Managementmentioning
confidence: 99%
“…39 Optimal approaches appear to involve a combination of inpatient and outpatient education, 40 which can also extend to caregivers (often close family members) 37 who often lack relevant healthcare knowledge. 41…”
Section: Health Educationmentioning
confidence: 99%
“…Social support has been shown to play a critical role in reducing patient stress associated with chronic diseases, 41,52 and the effect of psychosocial factors noted in the progression of HF. 41 Medicine and treatment adherence rates have been found to increase when social support is present for CHF and CVD patients, 53,54 which can be categorized into three types: patient-to-patient, patient-tofamily, and patient-to-provider.…”
Section: Peer and Community Supportmentioning
confidence: 99%